2005
DOI: 10.1016/j.devcel.2004.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Organization by the Septin Cytoskeleton Is Essential for Structural and Mechanical Integrity of Mammalian Spermatozoa

Abstract: Septins are polymerizing GTP binding proteins required for cortical organization during cytokinesis and other cellular processes. A mammalian septin gene Sept4 is expressed mainly in postmitotic neural cells and postmeiotic male germ cells. In mouse and human spermatozoa, SEPT4 and other septins are found in the annulus, a cortical ring which separates the middle and principal pieces. Sept4-/- male mice are sterile due to defective morphology and motility of the sperm flagellum. In Sept4 null spermatozoa, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
291
0
8

Year Published

2007
2007
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 256 publications
(315 citation statements)
references
References 37 publications
10
291
0
8
Order By: Relevance
“…This expression pattern suggests that SEPT7 may be involved in the regulation of the formation of the midpiece and annulus. Previous studies showed that SEPT1/4/6/7/12 are located at the sperm annulus and that this septin-based organization is a requisite for the structural and functional integrity of sperm [7,8,11,23]. Other proteins located at the mouse sperm annulus include DNAJB13 [24] and testis anion transporter 1 (TAT1) [25].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This expression pattern suggests that SEPT7 may be involved in the regulation of the formation of the midpiece and annulus. Previous studies showed that SEPT1/4/6/7/12 are located at the sperm annulus and that this septin-based organization is a requisite for the structural and functional integrity of sperm [7,8,11,23]. Other proteins located at the mouse sperm annulus include DNAJB13 [24] and testis anion transporter 1 (TAT1) [25].…”
Section: Discussionmentioning
confidence: 99%
“…The surplus cytoplasm is completely removed around the time of ejaculation via an unidentified mechanism [33]. Considering that Septin4 knockout mice also exhibit increased rates of immature sperm [7,8], SEPT4/7 may participate jointly in the regulation of the removal of the residual cytoplasm during sperm maturation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations